Obesity and menopausal transition - Ojeda-Lazo, Eliana (2025)
Obesity is a chronic multifactorial disease influenced by biological, psychological, andenvironmental determinants, with a higher prevalence in women. It is associated withchronic inflammation, metabolic disturbances, and an increased risk of cardiovasculardiseases and cancer. In postmenopause, the hormonal changes characteristic of thisstage affect body composition and energy metabolism, promoting an increase invisceral adiposity. Oestrogen decline favours fat redistribution towards the abdomen,which increases insulin resistance and the prevalence of metabolic syndrome. Thisprocess is accompanied by a reduction in resting energy expenditure and lean mass,without significant variations in body mass index (BMI). It is important to emphasisethat body fat distribution is a more accurate predictor of cardiometabolic riskthan BMI. Additionally, obesity influences the menopausal transition, exacerbatingsymptoms such as hot flushes, sleep disorders, and sexual dysfunction, as well asincreasing the risk of urinary incontinence, sleep apnoea, and cognitive impairment,partly due to systemic inflammation induced by adipokines. Moreover, obesityalso increases the risk of cancer, particularly endometrial and breast cancer, as itis associated with greater exposure to endogenous oestrogens. Given the increasein life expectancy, a growing number of women will spend a significant portionof their lives in postmenopause, a stage in which obesity is highly prevalent. Thisunderscores the need to address obesity as a priority public health issue due to itsimpact on quality of life and the risk of chronic diseases.